IMPLEMENTASI SISTEM INFORMASI MANAGEMEN KEUANGAN DAERAH (SIMDA) TERHADAP KUALITAS LAPORAN KEUANGAN - Suci; Abid Ramadhan; Asriany Asriany; I Ketut Patra (Jurnal Ilmiah Raflesia Akuntansi, 2022)
The Regional Financial Management Information System (SIMDA) is a tool for detecting the quality of regional financial reports and assisting the process of financial and development supervision. This study aims to empirically test the implementation of the Regional Financial Management Information System (SIMDA) on the Quality of the Palopo City Government Financial Reports, especially the Regional Revenue Agency (BAPENDA) of Palopo City. The variables used in this study, namely the independent variable (Implementation of Regional Financial Management Information System (SIMDA)) while the dependent variable (Quality of Financial Reports). The type of research used is descriptive quantitative approach using survey method. The population of this research is employees whose names are registered with the Regional Revenue Agency (BAPENDA). The sampling technique used was the purposive sampling method. The data analysis technique used in this study is simple linear regression using the SPSS Version 22 program. The results of the regression test show that the coefficient value of the Regional Financial Management Information System Implementation (SIMDA) of 0.397 has a positive effect on the Quality of Financial Statements, and the results of partial hypothesis testing (test t) Implementation of Regional Financial Management Information System affects the Quality of Financial Reports.